A path twice traveled my journey as a historian of China - Cohen, Paul A. (Cambridge, Massachusetts The Fairbank Center for Chinese Studies at Harvard University, 2019)
"Cohen, one of the West's pre-eminent historians of China, traces the development of his work from its inception in the early 1960s to the present, offering fresh perspectives that consistently challenge readers to think more deeply about China and the historical craft in general"--Provided by publisher.
Beginnings -- Wang Tao: the problem of change in the Late Qing -- The next step: discovering history in China -- Discovering history in China: the back story -- Limits of the China-centered approach -- A multiplicity of pasts: history in three keys -- History in three keys: research, writing, and publishing history -- Between history in three keys and speaking to history: surprise -- Developments -- The problem of insideness vs. outsideness: speaking to history -- The power of story: history and popular memory -- Then and now: the two histories.
Includes bibliographical references and index.
Keywords: Cohen, Paul A; Historians -- United States -- Biography; China -- Historiography